Towards a Risk-Based Continuous Auditing-Based Certification for Machine Learning - Dorian Knoblauch; Jürgen Großmann (The Review of Socionetwork Strategies, 2023)
Machine learning systems have gained widespread adoption across various industries. This includes highly regulated ones that need to match certain quality requirements based on a given risk exposure. The MLOps paradigm, following a similar approach to DevOps, promises major improvements in quality and speed, with a focus on deploying ML models at a fast pace with high quality on an automated basis. However, traditional point-in-time certifications with manual audits are inadequate for MLOps setups due to frequent changes to the ML system. To overcome this challenge, we propose Continuous Audit-Based Certification (CABC), which uses automated audits to issue or revoke certificates based on an automated assessment of artifacts from the MLOps lifecycle. Our approach utilizes artifacts from the MLOps lifecycle for quality measurements based on standards such as ISO 25012. We propose a risk-based measurement selection, an audit API for standardized retrieval of data for measurement, a tamper-proof data collection process, and an architecture for separation of duties in the certification process. CABC aims to improve efficiency, enhance trust in the ML system, and support highly regulated industries in achieving their quality goals.
Keywords: 300; MLOps; Machine learning quality dimensions; Certification